Assessment of Water Use and Willingness to Pay for Domestic Water among Residents in Binh Duong and Cao Duc Communes, Gia Binh District, Bac Ninh Province - Tuan Quynh, Tran Van; Khiem, Tran Van; Thi Huyen Trang, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 2, 2026)
Abstract: This study investigates the current status of domestic water usage and assesses the willingness to pay (WTP) for clean water among residents in Binh Duong and Cao Duc communes, Gia Binh district, Bac Ninh [1] province. Based on compiled data and interviews with 125 households, the research applies the contingent valuation method to determine WTP, using linear regression analysis in Stata 17, combined with Pearson correlation analysis and multicollinearity tests to develop the WTP model. The results show that 100% of households have access to piped water; however, over one-third still use rainwater for drinking purposes. The average WTP values for three water-use models are 213,250 VND/m³ (for drinking water), 9,770 VND/m³ (for other domestic uses), and 14,340 VND/m³ (for overall domestic water). The average domestic water cost of households in Binh Duong and Cao Duc communes is 193,590 VND per household per month, accounting for 1.3% of total household income. Four factors significantly influencing WTP include household income, education level, gender, and age of the household head. By 2050, the local population is projected to reach approximately 17,000, increasing water demand by about 630 m³/day compared to 2024. Based on these findings, the study proposes integrated solutions in infrastructure, communication, and policy to ensure sustainable domestic water supply in the future.